Microencapsulation of betalains obtained from cactus fruit (Opuntia ficus-indica) by spray drying using cactus cladode mucilage and maltodextrin as encapsulating agents - Otalora Rodriguez, Maria Carolina (2015)
The microencapsulation of betalains from cactus fruit by spray drying was evaluated as a stabilization strategy for these pigments. The betalains used as active agent were extracted from purple fruits of Opuntia ficus-indica (BE) and encapsulated with maltodextrin and cladode mucilage MD-CM and only with MD. The microcapsulates were characterized by scanning electron microscopy (SEM), thermal analysis (TGA-DSC), tristimulus colorimetry, as well as, their humidity, water activity and dietary fiber content were also determined. The active agent content was measured by UV-Vis spectrophotometry and its composition confirmed by HPLC-ESIMS. A pigment storage stability test was performed at 18 C and different relative humidities. The addition of CM in the formulation increased the encapsulation efficiency, diminished the moisture content, and allowed to obtain more uniform size and spherical particles, with high dietary fiber content. These microencapsulates are promising functional additive to be used as natural colorant in the food industry.